The cat's meow : how cats evolved from the Savanna to your sofa - Losos, Jonathan B. (Viking, an imprint of Penguin Random House LLC, 2023)
"The past, present, and future of the world's most popular and beloved pet, from a leading evolutionary biologist and great cat lover The domestic cat-your cat-has, from its evolutionary origins in Africa, been transformed in comparatively little time into one of the most successful and diverse species on the planet. Jonathan Losos, writing as both a scientist and a cat lover, explores how researchers today are unraveling the secrets of the cat, past and present, using all the tools of modern technology, from GPS tracking (you'd be amazed where those backyard cats roam) and genomics (what is your so-called Siamese cat . . . really?) to forensic archaeology. In addition to solving the mysteries of your cat's past, it gives us a cat's-eye view of today's habitats, including meeting wild cousins around the world whose habits your sweet house cat sometimes eerily parallels. Do lions and tigers meow? If not, why not? Why does my cat leave a dead mouse at my feet (or on my pillow)? Is a pet ocelot a bad idea? When and why did the cat make its real leap off the African plain? What's with all those cats in Egyptian hieroglyphics? In a genial voice, casually deciphering complex science and history with many examples from his own research and multi-cat household, Losos explores how selection, both natural and artificial, over the last several millennia has shaped the contemporary cat, with new breeds vastly different in anatomy and behavior from their ancestral stock. Yet the cat, ever a predator, still seems only one paw out of the wild, and readily reverts to its feral ways as it occupies new lands around the world. Humans are transforming cats, and they in turn are transforming the world around them. This charming and intelligent book suggests what the future may hold for both Felis catus and Homo sapiens"--